The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/jmv.1890400409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of canine distemper antibodies in the pagetic population

Abstract: Recent molecular evidence has implicated canine distemper virus (CDV) as a possible aetiologic agent in Paget's disease. However, previous serological studies have shown no differences in levels of anti-CDV antibodies between Paget's patients and controls. In this study, the technique of enzyme linked immunosorbent assay was used to measure anti-CDV antibodies in a group of Paget's patients from the North West of England. Some patients were undergoing treatment with 3-amino-hydroxypropylidene (APD), and the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Thereafter, and similar to the MS controversy, an association between household pets and PDB was made by epidemiological studies (O'DRISCOLL; ANDERSON, 1985;O'DRISCOLL et al, 1990), and this likelihood was increased when mongrels or unvaccinated dogs were evaluated (KHAN et al, 1996). Studies using in situ hybridisation have observed that only CDV-N antisense probes hybridized with CDV RNA within osteoclasts, osteoblasts, and osteocytes of patients with PDB (GORDON; ANDERSON; SHARPE, 1991;GORDON et al, 1993); similar results were also observed with in situ-reverse RT-PCR (MEE et al, 1998). Further, CDV N gene was identified by in situ hybridisation and RT-PCR from bone cells of dogs diagnosed with metaphyseal osteopathy , a canine bone disease of uncertain etiology but with some similar histological features of PDB .…”
Section: Public Health Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, and similar to the MS controversy, an association between household pets and PDB was made by epidemiological studies (O'DRISCOLL; ANDERSON, 1985;O'DRISCOLL et al, 1990), and this likelihood was increased when mongrels or unvaccinated dogs were evaluated (KHAN et al, 1996). Studies using in situ hybridisation have observed that only CDV-N antisense probes hybridized with CDV RNA within osteoclasts, osteoblasts, and osteocytes of patients with PDB (GORDON; ANDERSON; SHARPE, 1991;GORDON et al, 1993); similar results were also observed with in situ-reverse RT-PCR (MEE et al, 1998). Further, CDV N gene was identified by in situ hybridisation and RT-PCR from bone cells of dogs diagnosed with metaphyseal osteopathy , a canine bone disease of uncertain etiology but with some similar histological features of PDB .…”
Section: Public Health Concernsmentioning
confidence: 99%
“…This study confirmed previous descriptions of the participation of CDV in natural and experimentally-induced bone lesions of young dongs (BAUMGÄRTNER et al, 1995b), but it is unknown if this represents a separate CDV-induced bone disease or a manifestation of systemic CDV (BAUMGÄRTNER et al, 1995a). The marked difference between the studies of experimental and natural CDV-induced infections of dogs and those with PDB was that both sense and antisense probes were bound to bone cells when in situ hybridization was used (BAUMGÄRTNER et al, 1995a), whereas only CDV sense probes were bound to bone cells in human cases of PDB (GORDON; SHARPE, 1991;GORDON et al, 1993).…”
Section: Public Health Concernsmentioning
confidence: 99%
“…Several attempts have been made to improve diagnosis of CD and several conventional RT-PCR assays have been developed that allow effective virus detection in vivo with high levels of sensitivity and specificity (Shin et al 1995, Frisk et al 1999. It is possible to detect viral nucleocapsid mRNA through RT-PCR (Del Puerto 2006), an important molecular tool in detection of acute and chronic infection, and post-mortem evaluation of CDV in different biological samples (Gordon et al 1993, Frisk et al 1999, Kim et al 2001, Hoyland et al 2003, Gebara et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…No statis tically significant differences in circulating levels of CDV anti bodies were reported between patients with Paget's disease and healthy individuals. 106 Three other studies in the UK reported no evidence of CDV transcripts in any patient with Paget's disease. 89,94,95 Respiratory syncytial virus Respiratory syncytial virus (RSV) is a pneumovirus of the Paramyxoviridae family, which is a common pathogen that causes respiratory infections in children and adults.…”
Section: Canine Distemper Virusmentioning
confidence: 93%